THE EFFECT OF THERMAL LOAD ON THE BODY OF OUTDOOR WORKERS: ANALYSIS BASED ON MEDICAL AND HYGIENIC INDICATORS - Ikramova N. A.; Mirsagatova M. R.; Jalolov N. N.; Kasimova Kh. T.; Sultonov E. Y.; Sadirova M. K. (The Conference Hub, 2025)
Industrial production activities along with service sectors see an annual rise in the number of employees who work outdoors. The workers in traffic police service alongside construction, utilities and agriculture and transportation units operate daily under variable climatic situations especially hot temperatures. Thermal load stands as the primary impacting physiological factor affecting human bodies in extreme temperature conditions because it affects both heat balance management and thermoregulatory systems.